2017
DOI: 10.1007/s41742-017-0001-y
|View full text |Cite
|
Sign up to set email alerts
|

Selective Electrodialysis for Copper Removal from Brackish Water and Coal Seam Gas Water

Abstract: This study investigates the removal rate of divalent ions during partial desalination of brackish water using electrodialysis (ED). An experiment was conducted with a benchtop PCCell electrodialysis instrument in batch mode with a non-ion selective membrane. The removal rate of total copper, a valuable plant micronutrient, was analysed. Both copper chloride and copper sulphate removal compared to sodium chloride removal were studied. The copper and the sulphate content in the diluate declined logarithmically w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…It should be noted that the condition δ (1) does not exist because the input layer is considered as observational values and is used as a training set. Therefore, there are no errors with input [27].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the condition δ (1) does not exist because the input layer is considered as observational values and is used as a training set. Therefore, there are no errors with input [27].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, awareness of the future status of water resources, especially in standard drinking water classes, is very important for urban and rural communities [1]. The level of groundwater resources is changing rapidly and this requires the discovery of newer groundwater resources [2].…”
Section: Introductionmentioning
confidence: 99%
“…Aligned with industry use, the literature has mainly investigated the monovalent selectivity of MSED for concentrated seawater salinities [11,12,13]. More recent studies have been conducted on recovery of nutrients, particularly ammonium and phosphate, from industrial and municipal wastewaters [8,14,15,16] and removal of sodium or nitrate from groundwater [17,18,19,20,21]. Ahdab et al [20,21] concluded that the Neosepta CMS/ACS membranes and Fujifilm Type 16 membranes are selective towards sodium for 16 diverse BGW compositions.…”
Section: Introductionmentioning
confidence: 99%
“…Purification of water can be achieved by physicochemical and biological methods. The physicochemical methods include precipitation [7], membrane filtration [8], liquid-liquid extraction [9] reverse osmosis [10], electrolysis or ultrasonic electrolysis [11], electrodialysis [12], electrodeposition [13], ion exchange resins [14], incineration and electrokinetic method [15], flotation [16], flocculation [17], coagulation [18], photocatalysis [19], adsorption and biosorption [20]. Biological process includes biodegradation or bioremediation [21], phycoremediation [22].…”
Section: Introductionmentioning
confidence: 99%